ANTIVIRAL SCREENING OF AZADIRACHTA INDICA PHYTOCHEMICALS AS DENGUE NS5 INHIBITOR: A MOLECULAR DOCKING APPROACH - NAWAZ, A; IJAZ, B (Biological and Clinical Sciences Research Journal, 2023)
Dengue has been an alarming viral infection in tropical and subtropical regions of the world for the past few decades, resulting in millions of deaths. There is no effective drug to treat this arbovirus-based infection. Dengue virus non-structural protein NS5 contains N terminus methyl transferase domain and C terminus RNA-dependent RNA polymerase domain, which is involved in viral RNA replication and serves as a potential target. The current in-silico study aims to find new potential dengue virus NS5 protein inhibitors. The designed library containing eight compounds from Azadirachta Indica was used to perform molecular docking against active residues of dengue virus NS5 protein. Four compounds (Desacetyl Salanin, Azadirchtin-A, Castalagin, Vilasinin) with high negative binding energy values and zero RMSD values were selected, and their drug-likeness and ADMET analysis was performed. Among the best-docked compounds, Vilasinin (-11kcal/mol) exhibited drug-like properties as it has a molecular weight less than 500 D and has zero violation value. Moreover, it has 5 hydrogen bond donors and 10 hydrogen bond acceptors. It is well soluble in water so that it can be used as a potential inhibitor and drug candidate for the treatment of dengue infection.